Desarrollo de los verticilos sexuales de Vanroyenella plumosa Novelo & Philbrick (Podostemaceae) - Murguía Sánchez, Guillermina; Novelo R., Alejandro; Philbrick, C. Thomas; Márquez Guzmán, G. Judith (Instituto de Ecología, A.C., 2001)
The vegetative body of Vanroyenella plumosa Novelo & Philbrick (subfamily Podostemoideae) is composed of roots, leaves and a dorsiventrally flattened thalloid stem which, in the reproductive stage of the life cycle, develops cavities containing fascicles of flowers. In this work the embryology of this species was studied. Floral development depends on the flower position in the vegetative body of the plant, the plant position on the rock and the water level in the river. Vanroyenella plumosa possesses two stamens with tetrasporangiate anthers; the anther wall formation is of the basic type. Tetrads are tetrahedral, and the pollen is bicellular. The gynoecium is bicarpelar and bilocular with axial placentation and has two stigmas with idioblasts whose vacuoles contain proteins and carbohydrates. The ovules are anatropous, bitegmic and tenuinucellate. The embryo sac is monosporic in its origin and tetracellular of the Apinagia type. In Vanroyenella floral development occurs in the interior of the stem while the plant is submerged, and it is during this very early stage that the male and female gametes are formed. When the water level recedes, the pedicels elongate and anthesis occurs above water. The ovary wall supports the seed development after the rest of the vegetative tissue has died.